Woolwich massage and back rolling are effective in increasing breast milk production in mothers with post-cesarean section indications of premature rupture of membranes (prom) in hospitals - Alfanira Alfanira; Suryani Hartati; Meiliyani Meiliyani (Science Midwifery, 2026)
Introduction: Premature rupture of the membranes (KPD) is one of the conditions that is a factor that causes the procedure to be performed by sectio caesarea because the prematurely ruptured membranes increase the risk to the mother and fetus. Cesarean delivery can lead to ineffective breastfeeding due to pain, stress, and separation between the mother and the baby in the NICU. Efforts are made to increase breast milk production, namely with Woolwich massage and back rolling. Objectives: The purpose of this study is to determine if the effectiveness of Woolwich massage and back rolling can increase breast milk production of post-cesarean section mothers with KPD indications in hospitals. Methods: This research method uses a descriptive method with a case study approach using postpartum nursing care carried out on April 28-Mei 3, 2025, for post-SC mothers on the indication of KPD. Results: The evaluation was carried out for 3 days, with the administration of Woolwich massage and back rolling twice a day for ±20 minutes. On the first day before the action was taken, the breast milk had not come out. After the massage, there began to be changes even though there was still very little breast milk. On the second day, breast milk production began to look more stable and was seen dripping until the fifth day, when the milk had begun to flow smoothly. Conclusion:  this study shows that the action of Woolwich massage and back rolling is proven to increase breast milk production in post-SC mothers with ineffective breastfeeding problems.